Circular economy ecosystems: a typology, definitions, and implications - Aarikka-Stenroos, Leena (Edward Elgar Publishing, 2021)
This innovative Research Handbook answers crucial questions about how individuals and organisations can make a difference towards sustainability. Offering an integrative perspective on sustainability agency, it reviews individual, active, organisational and relational forms of sustainability agency, demonstrating the capacity of individuals and organisations to act toward sustainable futures.